AI in the Teaching-Learning of Languages - D’Esposito, Maria Eugenia Witzler; Gatner, Sérgio (The ESPecialist, 2024)
The aim of this paper is to present the concepts of artificial intelligence (AI) (UNESCO, 2019 a,b, 2021; Luckin, 2019, 2021; Luckin, George & Cukurova, 2022) and artificial intelligence in education (AIEd) and how this autonomous adaptive system can help all agents in the teaching-learning process. We will present a few tools and platforms that can be used for teaching-learning of languages, challenges and limitations related to the use of AIEd (Luckin et al., 2016). This work is relevant as AI impacts social relations, various organizational processes and education. Furthermore, the Beijing consensus (UNESCO, 2019c) proposes the integration of AI technologies in education to help us achieve the sustainable development goals and the 2030 agenda for education (UNESCO, 2017).